Lawful rights of mankind: an introduction to the international legal code of human rights - "Sieghart, Paul" (New York, 1986)
Paul Sieghart now brings together for the first time in one volume all the substantive international law of human rights. He first introduces the subject and then considers, one by one, the approximately forty rights, with full cross references.
Keywords: Civil rights (International Law)